Present Status of Aquatic Resource and Its Catch of Mogra River in Bangladesh - B. K., Chakraborty; A. K., Verma; S., Muniya (Sustainable Marine Structures, 2021)
Bangladesh is very rich in aquatic fauna with a biodiversity. The present study, conducted during 2015 to 2019, recorded a total number of 131 spe cies (104 fish, 09 prawn, 01 snail, 04 crabs, and 13 turtles) belonging to 26 families were identified from the Mogra River and its flood plain. About ten types of fishing gears, different crafts, hook and line were found oper ative in the river. Increasing rates of using current jal (16.0-26.40%) and Kapuri jal (11.0-16.70%) were identified as detrimental gears destroyingdifferent species. The fish productivity was decreased dramatically from 170.63±10.81mt to 134.75±8.02 mt with a decreasing percentage of 6.26 to 21.03% within five years. Three important aquatic species turtiles (Cyclemys oldhami, Melanocheelys trjuuga and Morenia petersi) became rare and 17 commercially important aquatic species were at the edge of extinction (critically endangered, CR). From the study, 67 species were recorded inthe endangered (EN) category, 20 species vulnerable status (VU), 11 species lower risk (LR), 07 species Least concern (LC) and 04 Data deficient (DF). To save the existing aquatic species in the studied riverine ecosystem and ensure better livelihood of the fishes, a team of local management committee, similar to the Hilsa fisheries management technology is needed. ER